Non-hormonal male contraception: A review and development of an Eppin based contraceptive - O'Rand, Michael G.; Silva, Erick J. R. [UNESP]; Hamil, Katherine G. (Elsevier B.V., 2016)
Developing a non-hormonal male contraceptive requires identifying and characterizing an appropriate target and demonstrating its essential role in reproduction. Here we review the development of male contraceptive targets and the current therapeutic agents under consideration. In addition, the development of EPPIN as a target for contraception is reviewed. EPPIN is a well characterized surface protein on human spermatozoa that has an essential function in primate reproduction. EPPIN is discussed as an example of target development, testing in non-human primates, and the search for small organic compounds that mimic contraceptive antibodies; binding EPPIN and blocking sperm motility. Although many hurdles remain before the success of a non-hormonal male contraceptive, continued persistence should yield a marketable product. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: EPPIN; Male contraception; Sperm; Semenogelin; Reproductive pharmacology